Kinerja Karyawan Ditinjau Dari Kompetensi dan Komitmen Organisasi - Tri Sinarti; Sudarmiatin Sudarmiatin; Agus Hermawan (Jurnal Manajemen Stratejik dan Simulasi Bisnis, 2022)
It must be admitted that Micro, Small and Medium Enterprises in Indonesia are very supportive of the economy. MSMEs are the most important pillars in the Indonesian economy. MSMEs are able to absorb a large number of workers. Manpower as a human resource is the most important element that drives the wheels of business. Quality human resources are needed to win business competition. This study aims to analyze the effect of competence and organizational commitment on the employee performance of MSMEs Nurul Aqiqah and Catering Palembang, South Sumatra. The entire population in the study was sampled, namely all 40 employees, the sample was taken by the census method (saturated sample). The research instrument scale uses a Likert scale. The source of data in this study is primary data collected using a questionnaire. To analyze the data used SPSS version 26 application. The analytical technique used is multiple linear regression analysis. The results showed that the variables of competence and organizational commitment simultaneously had a significant effect on employee performance. Partially, the variables of competence and organizational commitment have a significant effect on employee performance. In conclusion, employee competence and organizational commitment are determinants of employee performance and automatically affect company performance.